Grapevine Leafroll: A Complex Viral Disease Affecting a High-Value Fruit Crop - Naidu, Rayapati; Rowhani, Adib; Fuchs, Marc; Golino, Deborah; Martelli, Giovanni P (Plant disease, 2014)
Grapevine (Vitis spp.) is one of the most widely grown fruit crops in the world. It is a deciduous woody perennial vine for which the cultivation of domesticated species began approximately 6,000 to 8,000 years ago in the Near East. Grapevines are broadly classified into red- and white-berried cultivars based on their fruit skin color, although yellow, pink, crimson, dark blue, and black-berried cultivars also exist. Grapevines can be subject to attacks by many different pests and pathogens, including graft-transmissible agents such as viruses, viroids, and phytoplasmas. Among the virus and virus-like diseases, grapevine leafroll disease (GLD) is by far the most widespread and economically damaging viral disease of grapevines in many regions around the world. The global expansion of the grape and wine industry has seen a parallel increase in the incidence and economic impact of GLD. Despite the fact that GLD was recognized as a potential threat to grape production for several decades, our knowledge of the nature of the disease is still quite limited due to a variety of challenges related to the complexity of this virus disease, the association of several distinct GLD-associated viruses, and contrasting symptoms in red- and white-berried cultivars. In view of the growing significance of GLD to wine grape production worldwide, this feature article provides an overview of the state of knowledge on the biology and epidemiology of the disease and describes management strategies currently deployed in vineyards.